Determinants of Financial Report Moderated by Quality Audit (Study of Multi-Industry Sector Companies Listed on the Indonesia Stock Exchange Period 2015 – 2019) - Sri Hidayati; Apollo Daito (Dinasti International Journal of Economics, Finance & Accounting, 2023)
This study aims to determine the effect of good corporate governance (GCG), company reputation, and company competence on the quality of financial reports with audit quality as a moderating variable. The population in this study are manufacturing companies in the various industrial sectors listed on the Indonesia Stock Exchange in 2015 - 2019 with a total of 185 companies. The method used was purposive sampling, 37 companies were selected as the research sample. The results of the study show that Good Corporate Governance (GCG) has no direct effect on the quality of the company's financial statements. Meanwhile, company reputation and company competence have a significant and positive effect on the quality of financial reports. After being moderated by audit quality, Good Corporate Governance (GCG), company reputation, and company competence have a positive and significant effect on the quality of financial reports.